The abundance and diversity of insects in the phytotelmata ecosystems of Rizal Park and Mehan Garden in relation to its abiotic factors - Arbiz, John Reyno P. Flores, Mill Jeanne Herrera, Danna Kristel M. Romero, Ridgeuel John R. 4 0 16; 5
ABSTRACT: This study investigates insect abundance and diversity in phytotelmata ecosystems of urban green spaces. The study focused on Rizal Park and Mehan Garden, with four sampling stations evenly distributed across the sites. Phytotelmata ecosystems were found using opportunistic sampling. Abundance and diversity data, along with abiotic variables, were collected weekly for one month. In Mehan Garden, there were 1,244 insects identified, composed of Aedes egypti (72.35%), Nilotanypus sp. (15.03%), and Psychoda sp. (12.62%). Rizal Park had a total of 5 species and 2,218 insects, with Aedes aegypti being the most abundant (86.65%) and Ormosia sp. the least (0.05%). Mehan Garden exhibited greater diversity (0.44) compared to Rizal Park (0.24), primarily due to species evenness. Simpson's index of diversity was used, and Pearson's moment correlation and Spearman's rho were employed to test relationships between variables. The temperature was the only physico-chemical property significantly related to abundance in both sites. Mehan Garden showed significant relationships between diversity and total dissolved solids (TDS) and pH, while Rizal Park did not have any significant water parameters. Precipitation and light intensity were significantly related to abundance in both sites, alongside this is atmospheric pressure for Mehan Garden and cloudiness and wind speed/direction for Rizal Park. Wind speed/direction consistently showed a significant relationship with diversity in both sites, with the addition of atmospheric pressure in Mehan Garden and light intensity and cloudiness in Rizal Park. Keywords: Phytotelmata, Weather factors, Physico-chemical parameters, Abundance, and Diversity
Undergraduate Thesis: (BS in Biology major in Ecology) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2